Plan de comunicación para mejorar la demanda de servicios en el Hotel Santa María, Huamachuco - provincia Sánchez Carrión, 2020 - Contreras Vergaray, Erika Jaquelina (2021)
The general objective of this research was to establish how the communication plan improves the demand for services in the Hotel Santa María, Huamachuco - Sánchez Carrión province, 2020, for which an applied descriptive design was developed, using a cuasi-experimental type . The study population was 115 guests on a monthly average and the 15 hotel workers, as a technique the survey was used and the questionnaire as an instrument. As a result, the level of the communication plan is regular, the level of demand for the pre-implementation service was regular. The proposal and implementation of the communication plan was developed in the months of November and December 2020. The t test of difference of the means (averages) has a significance level of 0.043 which is less than 0.05; This allows us to accept the hypothesis "The communication plan significantly improves the demand for services at the Hotel Santa María, Huamachuco - Sánchez Carrión province." Finally, the level of service demand after implementation is good.